Prevalence of malaria and contributing factors in children under five years of age attending Nakasongola General Military Hospital. A cross-sectional study. - Asiimwe, Stephen; Anywar, Lydia (SJ Insights, 2025)
Background. Children under 5 years old are the group most vulnerable to malaria infection because of less developed immune systems. This study aimed to determine the prevalence of malaria and contributing factors in children under five (5) years of age who attend the OPD in Nakasongola General Military Hospital. Methods. A descriptive cross-sectional study was used employing a quantitative approach to data collection. The caregivers of children below five years of age who were sent to the laboratory for malaria testing were requested to participate in the study, and those willing were enrolled until the required sample size was reached. Data on socioeconomic factors and coverage of ITN use were collected using a pretested structured questionnaire. Data were analyzed using SPSS version 27 software, and results were presented in tables and graphs. Results. 66 (53.2%) of these children were males, 30 (24.2%) were between 12 and 23 months of age, and the overall prevalence of malaria was 44.4%. Among the malaria-positive children, 60.0% were males and between 36 and 47 months of age (25.5%). Malaria infection was associated with low caregivers’ age (38.2%) among caregivers 15 – 19 years old, rural residence (70.9%), primary level education (56.4%), and peasant farming (30.9%). Children who slept under ITNs were more likely to be protected from malaria infection (98.3%). Conclusion. Malaria infection is highly prevalent in children aged between 36 and 47 months. Socioeconomic factors, such as the age and education level of the household head, use of mosquito bed nets for sleeping, place of residence, and age of the children, were significant factors associated with malaria prevalence among children under 5 years of age. Recommendations. National studies should be conducted to identify the different geographical regions of the country that are most at risk of malaria, using updated malaria risk maps.